Limnological evolution of Zelma Lake, a recently drained thermokarst lake in Old Crow Flats (Yukon, Canada) - Tondu, Jana; Turner, Kevin W.; Wiklund, Johan A.; Wolfe, Brent B.; Hall, Roland I.; McDonald, Ian (NRC Research Press (a division of Canadian Science Publishing), 2016)
Evidence from remote sensing studies suggests that the frequency of thermokarst lake drainage events is increasing in response to climate change, but the consequences of these changes on the limnology of remaining waterbodies is unknown. Here, we utilize a multi-parameter paleolimnological record and post-drainage water isotope and chemistry monitoring to characterize the limnological evolution of Zelma Lake, in Old Crow Flats (OCF), Yukon. During the early part of the record (~1678 to 1900 CE), analysis of geochemical parameters and algal pigments indicate relatively stable limnological conditions. Abruptly beginning at ~1900, Zelma Lake experienced a 40-year phase of reduced production likely resulting from thermokarst shoreline expansion and associated increases in turbidity and low light availability. This was followed by ~70 years of increasing production, likely from the stabilization of shorelines combined with a warming climate. Zelma Lake catastrophically drained in June 2007. Post-drainage conditions were characterized by intense eutrophication marked by increases in nutrient and major ion concentrations and the unprecedented occurrence of okenone and diatoxanthin pigments. Comparison to the post-drainage paleolimnological record from another thermokarst lake in OCF indicates sharp increase of production is likely a common outcome of thermokarst lake drainage, yet intensity differs owing to site-specific catchment characteristics The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.